Seer: Predictive Runtime Kernel Selection for Irregular Problems - Swann, Ryan; Osama, Muhammad; Sangaiah, Karthik; Mahmud, Jalal (Proceedings / International Symposium on Code Generation and Optimization, 2024)
Modern GPUs are designed for regular problems and suffer from load imbalance when processing irregular data. Prior to our work, a domain expert selects the best kernel to map fine-grained irregular parallelism to a GPU. We instead propose Seer, an abstraction for producing a simple, reproduceable, and understandable decision tree selector model which performs runtime kernel selection for irregular workloads. To showcase our framework, we conduct a case study in Sparse Matrix Vector Multiplication (SpMV), in which Seer predicts the best strategy for a given dataset with an improvement of 2× over the best single iteration kernel across the entire SuiteSparse Matrix Collection dataset.